In competency Aspects of Microfinance Industry: Via SFA approach - Riaz, Madiha (Journal of Economics and Behavioral Studies, 2015)
Microfinance is a well known terminology used for microcredit and financial services for financially deprived community. Through informal, semi-formal and formal ways different institutions has been providing these services. Expenditure of the industry is considered to be high because of its inherent structure, dealing with small loans and having high risk of recovery. Therefore, expected inefficiency is greater than its profit. There are several factors and reason. Through this study, we analyzed few factors which have a positive or negative relation with the inefficiency of Microfinance in Pakistan. Stochastic frontier analysis (SFA) is used for weighing up a relationship between inefficiency and its determinants. It is seen that the average efficiency of this sector is low, on average the highest technical efficiency score is 87 only. Age and number of clients have a negative relationship with inefficiency whereas for other variable’s relationship is conditional on Microfinance Institutions (MFIs) working status. The number of women borrowers and average loan balance has been incorporated in the study to analyze the focus of MFIs, either on mission drift or achievement. We found that microfinance banks (MFBs) are drifting away, however, Non Government Organizations (NGOs) and Rural Support Programs (RSPs) are fulfilling their social mission efficiently. We did not find a strong evidence of mission drift in the industry because microfinance banks considered their social mission on second priority. Hence, if MFBs are drifting away from their social services, it is not unexpected.